Implementation Of Affine Cipher Combination And Merkle Hellman On The Process Digital Image Security - Achmad Fauzi; Husnul Khair; Muhammad Fadillah Azmi (Yayasan Kita Menulis, 2023)
The use of image media information has several weaknesses, one of which is the ease with which it can be manipulated by irresponsible people. Efforts made in increasing the security of this image is cryptography, namely the science and art of maintaining the security and confidentiality of images. Cryptography is used so that the confidentiality of the image can be maintained, so that it is not known by others. In general, there are 2 (two) techniques for carrying out cryptographic processes, namely encryption and decryption. In this study, the encryption process was first carried out using the Affine Cipher algorithm and then continued with the Merkle Hellman algorithm, while the decryption was carried out first by Merkle Hellman and then decrypted again with the Affine Cipher. The results of this study indicate that applying the Affine Cipher and Merkle Hellman algorithms can secure images. At the end of this system is an image that is in the form of blur so that it is not known and not understood by others. That way people who are not entitled cannot understand from the image.